Why a pluralist economics education is important for incarcerated individuals. (3rd February 2020) - Strenio, Jacqueline
An economics education provides students with the tools necessary to solve today's complex problems and additionally, is desirable among employers. This is true for both traditional college students and incarcerated individuals enrolled in college courses in the USA. This article reviews the literature on the benefits of correctional education, arguing explicitly for the inclusion of economics in college-in-prison programs. Using the experience of teaching economics in a state prison, I extrapolate on how key economic principles can be made relevant in incarcerated lives. The necessity for diversity in economic content, especially within the limitations of a college-in-prison economics course, is also explored. A pluralist approach to economics encourages students to think critically about economic theory and allows for the incorporation of work by a diverse set of scholars that may more closely resemble the incarcerated population. Additional pedagogical considerations to contemplate when teaching in correctional education programs are briefly highlighted.